Internalization of Foldamer-Based DNA Mimics through a Site-Specific Antibody Conjugate to Target HER2-Positive Cancer Cells - Valentina Corvaglia (Pharmaceuticals, 2021)
Inhibition of protein–DNA interactions represents an attractive strategy to modulate essential cellular functions. We reported the synthesis of unique oligoamide-based foldamers that adopt single helical conformations and mimic the negatively charged phosphate moieties of B-DNA. These mimics alter the activity of DNA interacting enzymes used as targets for cancer treatment, such as DNA topoisomerase I, and they are cytotoxic only in the presence of a transfection agent. The aim of our study was to improve internalization and selective delivery of these highly charged molecules to cancer cells. For this purpose, we synthesized an antibody-drug conjugate (ADC) using a DNA mimic as a payload to specifically target cancer cells overexpressing HER2. We report the bioconjugation of a 16-mer DNA mimic with trastuzumab and its functional validation in breast and ovarian cancer cells expressing various levels of HER2. Binding of the ADC to HER2 increased with the expression of the receptor. The ADC was internalized into cells and was more efficient than trastuzumab at inhibiting their growth in vitro. These results provide proof of concept that it is possible to site-specifically graft high molecular weight payloads such as DNA mimics onto monoclonal antibodies to improve their selective internalization and delivery in cancer cells.